Identification of the change in the profile of renal markers associated with SARS-CoV-2 infection (Research, Society and Development, 2022)
Kidney injury is a syndrome characterized by reduced kidney function and is an important finding in hospitalized patients. Studies have shown significantly elevated levels of renal biomarkers in patients infected with COVID-19. Therefore, the objective of this literature review was to describe changes in renal markers in laboratory tests of hospitalized patients with COVID-19, reporting on the problems caused to the human organism related to infection, the effects of infection on the renal system of hospitalized patients and changes in renal markers in infected patients. It is a theoretical framework developed through the search of publications obtained in the databases: PubMed and SciELO, published in the last 3 years. The descriptors SARS-CoV-2, Renal Failure and Renal Markers were used. Through the analysis of the survey of all the material, it was possible to demonstrate that 25% of hospitalized patients with COVID-19 develop renal failure, presenting an increase in urea and creatine levels, a decrease in the rate of GFR, and the presence of proteinuria and hematuria in the exams. of urine. Regarding complications resulting from SARS-CoV-2 infection, the respiratory, cardiovascular, renal, hepatic, gastrointestinal and neurological systems were the most reported. Given the importance of maintaining kidney integrity and screening through biochemical markers, more research on this topic is needed to improve understanding of kidney damage in COVID-19 cases and its health impact.